2010
DOI: 10.1017/s0029665110004519
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and oral nutritional supplements – a 360° approach to understanding management and compliance

Abstract: Malnutrition is often the cause or the consequence of ill health (1) . BAPEN (2009) reports that care pathways for the identification and treatment of malnutrition are complex and often knowledge of the condition is poor among health-care professionals (HCP) (2) , many of whom have not received training in nutrition. Oral nutritional supplements (ONS) can play a key role in the management of malnutrition, and yet compliance is often perceived as poor.Two complementary studies that examine different aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Patients report poor flavour quality of ONS, including overall flavour type, unbalanced flavour profile, off notes/taints or undesirable aftertastes and sensations, both anecdotally and, in the literature, is frequently linked to low levels of adherence (11,12,28,40,53,67,81,82). Numerous studies have found that perception of poor flavour is an important factor limiting product liking and adherence to ONS (15,44,53,67,83,84).…”
Section: Flavourmentioning
confidence: 99%
“…Patients report poor flavour quality of ONS, including overall flavour type, unbalanced flavour profile, off notes/taints or undesirable aftertastes and sensations, both anecdotally and, in the literature, is frequently linked to low levels of adherence (11,12,28,40,53,67,81,82). Numerous studies have found that perception of poor flavour is an important factor limiting product liking and adherence to ONS (15,44,53,67,83,84).…”
Section: Flavourmentioning
confidence: 99%
“…Patients have reported poor flavor quality of ONS, including overall flavor type, unbalanced flavor profile, off notes/taints, or unfavorable aftertastes and sensations, anecdotally in the literature [14][15][16] . Numerous studies have discovered that inadequate flavor perception dramatically reduces product acceptance and ONS adherence 17,18 . Nutritional components employed in ONS formulations result in several sensory problems, including taints and aftertastes 19 .…”
Section: Discussionmentioning
confidence: 99%